Mentoring the SEHATI Program for Food and Beverage MSMEs to Establish a KHAS Zone in Gejlig Village - Adinugraha, Hendri; Rahmawati, Ferida; Nafilah, Nafilah; Dewi, Anggun Rahadian Kusuma; Najwa, Nehyatul (Joong-Ki : Jurnal Pengabdian Masyarakat, 2025)
This community service program was implemented to address the low level of halal certification among food and beverage MSMEs in Gejlig Village, which has the potential to weaken business competitiveness. The Free Halal Certification Program (SEHATI) was chosen as a strategic solution to enhance MSME capacity while promoting the Halal, Safe, and Healthy Culinary Zone (KHAS). The objective of this program is to improve the knowledge, technical skills, and administrative capabilities of business actors, enabling them to meet halal and thayyib standards consistently. The method employed was Participatory Action Research (PAR), involving MSMEs, village government, BUMDes, academics, and halal inspection institutions in the planning, training, mentoring, and evaluation processes. The results show that most MSMEs completed the stages of socialization, technical training, administrative mentoring, and field verification, with 66.7% achieving halal certification. Beyond improving technical competence and administrative literacy, the program also fostered collective community awareness of the importance of the halal culinary ecosystem. Therefore, the SEHATI Program has proven effective in accelerating the transformation of MSMEs into competitive halal businesses and supporting the realization of Gejlig Village as a sustainable KHAS Zone.